Free love a novel - Hadley, Tessa 1956- (Harper, an imprint of HarperCollins Publishers, 2022)
"1967. While London comes alive with the new youth revolution, the suburban Fischer family seems to belong to an older world of conventional stability: pretty, dutiful homemaker Phyllis is married to Roger, a devoted father with a career in the Foreign Office. Their children are Colette, a bookish teenager, and Hugh, the golden boy. When the twenty-something son of an old friend pays the Fischers a visit one hot summer evening, and kisses Phyllis in the dark garden after dinner, something in her catches fire. Newly awake to the world, Phyllis makes a choice that defies all expectations of her as a wife and a mother. Nothing in these ordinary lives is so ordinary after all, it turns out, as the family's upheaval mirrors the dramatic transformation of the society around them..." --
"First published in the United Kingdom in 2022 by Jonathan Cape, an imprint of Vintage"--Title page verso
Keywords: London (England) / 20th century / Fiction; Families / Fiction; Mothers / Fiction; Wives / Fiction; Nineteen sixties / Fiction; Familles / Romans, nouvelles, etc; Mères / Romans, nouvelles, etc; Femmes mariées / Romans, nouvelles, etc; Années soixante (Vingtième siècle) / Romans, nouvelles, etc; FICTION / Literary; FICTION / Psychological; FICTION / Family Life / General; Families; Nineteen sixties; Psychological fiction; Women / Sexual behavior; England / London; London (England) / Fiction; Domestic fiction; Historical fiction; Romance fiction; Love stories; Fiction